Understanding variability and repeatability of enteric methane production in feedlot cattle - Beauchemin, Karen A.; Tamayao, Paul; Rosser, Christine; Terry, Stephanie A.; Gruninger, Robert (Frontiers in Animal Science, 2022)
Breeding ruminants for low methane (CH4) emissions can be permanent and cumulative, but requires a better understanding of the variability of CH4 production among animals to accurately assess low-CH4 phenotypes. Our objectives were to: 1) investigate the variation in CH4 production among and within growing beef cattle, 2) identify low-CH4 emitters, and 3) examine relationships between CH4 production and intake, feeding behavior, growth, and rumen fermentation. Crossbred beef heifers (n=77; body weight=450 kg) were allocated to 3 pens and offered a finishing diet of 90% concentrate and 10% silage (dry matter (DM) basis). The study was conducted over 3 consecutive 6-week periods (126 days). GrowSafe bunks measured individual animal DM intake (DMI) and rumen fluid was sampled orally each period. A GreenFeed system measured individual animal emissions for 2 weeks/period. Methane production was calculated by animal within period using visits that were ≥3 min with fluxes compiled into six 4-h blocks corresponding to time of day, and averaged over blocks to obtain an average daily emission for the period. Only animals with ≥2 periods of complete CH4 data were used in the final analysis (n=52). Animals were ranked based on CH4 yield (g/kg DMI) from low to high, and grouped as Very-low (≤10% of animals), Low (11-25%), Intermediate (26-74%), High (75-89%), and Very high (≥90%) emitters (mean±SD, 12.63±2.162). CH4 yield was 16% less (P<0.05) for Very-low compared with Intermediate animals due to lower CH4 production (g/d, P<0.05) rather than decreased DMI (P>0.05). Total VFA concentration decreased as CH4 yield decreased, although molar proportions of VFA remained unchanged, suggesting lower extent of ruminal digestion rather than a shift in fermentation. There were no differences in feeding behavior or average daily gain among groupings (P>0.05). A period × grouping interaction (P<0.001) for CH4 yield indicated that the rankings for animals changed over time, although there were no extreme changes in rankings. We conclude that when using a GreenFeed system, strict protocols need to be employed with measurements repeated over time to accurately identify low CH4-emmitting beef cattle.